IN SERVICE ENGLISH TEACHERS’ PERCEPTION OF JOINING ICT BASED TEACHER TRAINING - Alawiyah, Utin Novianti; Farikhah, Ni'matul (Jurnal Penelitian Humaniora, 2023)
This study aims to investigate in-service English teachers’ perception toward experience in joining ICT-based teacher training and describe the impact of joining ICT-based teaching training on in-service English teachers’ teaching. This research study uses a narrative inquiry design to analyze the data from observation and semi-structured interviews. Observations were used to know the significant impact of joining ICT-based teaching training on in-service English teachers’ teaching, while interviews were to investigate in-service English teachers’ perceptions toward experience in joining ICT-based teacher training. The result showed that in-service teachers faced several obstacles in joining the training. However, the teacher also gained more knowledge about technology related to their teaching. The impact of the training is that in-service English teachers know more about the procedure to improve their ICT teaching. The training has greatly impacted in-service English teachers in developing new teaching methods.